2015
DOI: 10.1086/682050
|View full text |Cite
|
Sign up to set email alerts
|

A Process-Independent Explanation for the General Form of Taylor’s Law

Abstract: Taylor's law (TL) describes the scaling relationship between the mean and variance of populations as a power law. TL is widely observed in ecological systems across space and time, with exponents varying largely between 1 and 2. Many ecological explanations have been proposed for TL, but it is also commonly observed outside ecology. We propose that TL arises from the constraining influence of two primary variables: the number of individuals and the number of censuses or sites. We show that most possible config… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
70
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(71 citation statements)
references
References 38 publications
1
70
0
Order By: Relevance
“…Such empirical ubiquity suggests that TL could be another of the so-called universal laws (26) like the laws of large numbers (27) and the central limit theorem (28). For example, independently of the present study, Xiao et al (29) showed numerically (not analytically) that random partitions and compositions of integers led to TL with slopes often between 1 and 2, as commonly observed in empirical examples of TL.…”
supporting
confidence: 74%
“…Such empirical ubiquity suggests that TL could be another of the so-called universal laws (26) like the laws of large numbers (27) and the central limit theorem (28). For example, independently of the present study, Xiao et al (29) showed numerically (not analytically) that random partitions and compositions of integers led to TL with slopes often between 1 and 2, as commonly observed in empirical examples of TL.…”
supporting
confidence: 74%
“…Importantly, this relationship applies to samples from different systems and does not pertain to cumulative patterns (e.g., collector's curves), which are based on resampling (20)(21)(22). Recent studies have also shown that N constrains universal patterns of commonness and rarity by imposing a numerical constraint on how abundance varies among species, across space, and through time (23,24). Most notably, greater N leads to increasingly uneven distributions and greater rarity.…”
mentioning
confidence: 99%
“…Another opportunity is to study 'within species over samples' characteristics. We point to the abundance-occupancy relation [33], to Taylor's law (fluctuation scaling [34] [35]) and to sampling theory [36]. Hopefully, all patterns can be integrated and applied for analysis with resampling statistics [37] (see also Wikipedia headwords 'Nonparametric statistics' and 'Resampling (statistics)') to obtain robust results, especially on the SAD.…”
Section: And Discussionmentioning
confidence: 99%